A centennial review of discoveries and advances in diabetes: Children and youth. Issue 7 (4th September 2022) - Mistry, Sejal; Tonyushkina, Ksenia N.; Benavides, Valeria C.; Choudhary, Abha; Huerta‐Saenz, Lina; Patel, Neha S.; Mahmud, Farid H.; Libman, Ingrid; Sperling, Mark A.
Abstract: Diabetes is an increasingly common chronic metabolic disorder in children worldwide. The discovery of insulin in 1921 resulted in unprecedented advancements that improved the lives of children and youth with diabetes. The purpose of this article is to review the history of diabetes in children and youth over the last century and its implications for future developments in the field. We identified 68 relevant events between 1921 and 2021 through literature review and survey of pediatric endocrinologists. Basic research milestones led to the discovery of insulin and other regulatory hormones, established the normal physiology of carbohydrate metabolism and pathophysiology of diabetes, and provided insight into strategies for diabetes prevention. While landmark clinical studies were initially focused on adult diabetes populations, later studies assessed etiologic factors in birth cohort studies, evaluated technology use among children with diabetes, and investigated pharmacologic management of youth type 2 diabetes. Technological innovations culminated in the introduction of continuous glucose monitoring that enabled semi‐automated insulin delivery systems. Finally, professional organizations collaborated with patient groups to advocate for the needs of children with diabetes and their families. Together, these advances transformed type 1 diabetes from a terminal illness to a manageable disease with near‐normal life expectancy and increased our knowledge of type 2 diabetes and other forms of diabetes in the pediatric population. However, disparities in access to insulin, diabetes technology, education, and care support remain and disproportionately impact minority youth and communities with less resources. The overarching goal of diabetes management remains promoting a high quality of life and improving glycemic management without undermining the psychological health of children and youth living with diabetes.